2009
DOI: 10.1080/03610920802571146
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Threshold Models

Abstract: This article focuses the attention on the Self Exciting Threshold Autoregressive Moving Average model (SETARMA) proposed in Tong (1983). The stochastic structure of the model is discussed and different specifications are presented. Starting from one of them, we give sufficient conditions for the weak stationarity of the model that are discussed and critically compared to other results given in literature. In particular, after showing that the SETARMA model belongs to the class of the Random Coefficients Autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Note that the multi-day SETAR model has the same skeleton model (noise free) for all days. Then, the conditions shown by Amendola et al (2009) for the SETAR model to be stationary are also sufficient conditions for the multi-day SETAR model to be stationary per day.…”
Section: Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…Note that the multi-day SETAR model has the same skeleton model (noise free) for all days. Then, the conditions shown by Amendola et al (2009) for the SETAR model to be stationary are also sufficient conditions for the multi-day SETAR model to be stationary per day.…”
Section: Modelmentioning
confidence: 94%
“…In practice, a handy tool is to run the skeleton model (noise-free model) with different initial conditions (Tong, 2010). Amendola et al (2009) showed that the SETAR model with two regimes ( 2) is weakly stationary if the matrices Φ (1) and Φ (2) have both dominant eigenvalues less than one, where…”
Section: Tar Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical properties of the TAR model and more detailed information can be seen in [28], [29] and [30]. In line with the potential of the TAR specification to distinguish multiple time series, we made use of the TAR specification for observing nonlinear associations, and the AR specification for observing linear associations in the multiple time series clustering task.…”
Section: Threshold Autoregressive Model (Tar)mentioning
confidence: 99%
“…Ling and Tong (2005) considered a quasi-likelihood ratio test for the threshold in moving average models. Amendola, et al (2009) discussed the stochastic structure of the self-exiting TARMA model; they specified sufficient conditions for weak stationarity and showed that the self-exiting TARMA model belongs to the class of the random coefficients autoregressive models. Smadi (1997) used the Bayesian approach for exploration of the joint posterior distribution for TARMA models using MCMC methods: he assumed noninformative priors, fixing the delay parameter d. In addition, he used a modified Gibbs sampling scheme, which is a hybrid strategy of Gibbs sampler, random walk Metropolis, and importance sampling.…”
Section: Introductionmentioning
confidence: 99%